Genotype 1 hepatitis E virus infection with acute acalculous cholecystitis as an extrahepatic symptom: a case report. Issue 1 (December 2016) - Fujioka, Ken; Nishimura, Toshiki; Seki, Masayuki; Kinoshita, Masanori; Mishima, Nobuyuki; Irimajiri, Shigeo; Yamato, Masaya
Abstract Background Hepatitis E virus (HEV) causes an acute viral hepatitis that is transmitted enterically. It is epidemic in Africa, Asia, the Middle East, and Central America. It is known that HEV can cause extrahepatic manifestations. Here, we report the first case of acalculous cholecystitis as an extrahepatic symptom of HEV. Case presentation A 24-year-old Japanese woman with no notable past medical history presented with complaints of fever and nausea while she was traveling in Australia; within the previous 2 months, she had also traveled to India and Africa. She visited a local hospital in Australia, and the laboratory tests showed significantly elevated levels of transaminase, so she was checked for viral hepatitis. After excluding hepatitis A, B, and C, as well as other causes of hepatitis, it was revealed that the patient was positive for HEV-IgM. Since she was a visitor to Australia, she was sent back to Japan and was transferred to our hospital. On day 4, the patient complained of right upper quadrant pain. Ultrasonography of the abdomen showed a thickened gallbladder wall without calculi. Acalculous cholecystitis was diagnosed from her course. No antibiotics were administered against it because there was no evidence of bacterial infection. The edematous wall showed significant improvement on day 11 and had returned to normal by day 14. The patient was discharged on day 16 because all of the symptoms had disappeared. Conclusions We found that HEV can cause acalculous cholecystitis as an extrahepatic manifestation. In addition, the cholecystitis could be resolved without any antibiotics.